Implementasi Program Kota Tanpa Kumuh Dalam Upaya Menambah Destinasi Wisata Baru Di Kota Palembang - Dwi Mirani; Sylvie Agustina; Rizki Ghoffar Ismail (Jurnal Empirika, 2019)
The arrangement of the urban area to be habitable for communities was declared by the government through the Kota Tanpa Kumuh (City without slums) or KOTAKUÂ  Program. The program has been implemented in several cities and districts in Indonesia. In Palembang, the implementation of KOTAKU Program has reached its third year, with a target zero of slum area in 2019. The purposes of this research were to study the implementation of KOTAKU Program in Palembang City, the factors that influence the success of the program and the participation model used by communities in the area of KOTAKU program. A descriptive format of the qualitative method was used in this study. This research focuses on the analysis of implementation using Merille S. Grindle's theory which is about the policy contents and the policy of the environment.Â  The result of the study indicated that the implementation of the KOTAKU Program in Palembang City has been successful but not fully optimal yet. This was caused by several inhibiting factors such us; topographic differences in each region, unsupportive local community behaviours, lack of government supports, socialization was not yet comprehensives and budget constraints. The community participation models that were used in the three observed regions were more on the physical participation of people who directly involved in the program. While, people who were not directly involved in the program, they were a lack of participation. However, this program still needs to be reviewed and evaluated continuously for achieving the target of 2019 Palembang slum zero areas.